2019
DOI: 10.1039/c9ay00105k
|View full text |Cite
|
Sign up to set email alerts
|

Two highly sensitive and selective coumarin-based fluorometric probes for the detection of ClO and cell imaging

Abstract: Two new coumarin-based fluorescent probes were synthesized and successfully applied for the efficient detection of ClO− as turn-on fluorescence chemosensors by the oxidative cleavage of C–O and CN, the detection limits (LOD) for the two probes are 154 nM and 32 nM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…With the increase of ClO − , the emission intensity of CCO at 530 nm was continuously and regularly enhanced. The fluorescence enhancement mechanism may be due to the redox reaction of the surface lactone groups of CCO . A more detailed information is found that the emission response of probe CCO to ClO − had a good linear relationship (R 2 =0.996) in the range of 0–8.5 μ M (Figure S4) .…”
Section: Resultsmentioning
confidence: 92%
“…With the increase of ClO − , the emission intensity of CCO at 530 nm was continuously and regularly enhanced. The fluorescence enhancement mechanism may be due to the redox reaction of the surface lactone groups of CCO . A more detailed information is found that the emission response of probe CCO to ClO − had a good linear relationship (R 2 =0.996) in the range of 0–8.5 μ M (Figure S4) .…”
Section: Resultsmentioning
confidence: 92%
“…In 2019, Jin and coauthors proposed two probes of the switch and turn-on types with a coumarin core, BCO and BETC, respectively (Fig. 7) [62]. Switching BCO (λ ex = 372 nm; λ em = 430/460 nm) and turning or C=O and C=N bonds (in the case of BETC) under the effect of HOCl with the formation of a common end product (NOA, Fig.…”
Section: Coumarin-based Probesmentioning
confidence: 99%
“…2 However, its uncontrolled production can cause cardiological diseases, cancer and tissue damage, 3,4 while hypochlorite residue in water gets converted into highly toxic constituents. 5,6 On a similar note, H 2 O 2 is also a reactive oxygen generator that serves as a signaling agent in cellular activities, helps in the removal of organic impurities from wastewater, 2,7–10 and acts as a common preservative. Nevertheless, excessive accumulation of H 2 O 2 results in intracellular oxidative stress and can cause pathological defects that lead to fatal diseases like cancer, genetic instability and diabetes.…”
Section: Introductionmentioning
confidence: 99%